Some Features of a Local Private Upper Gastrointestinal Endoscopic (UGIE) Practice Particularly Dyspeptic Symptoms Predictive Value of the result A prospective analysis of 1700 cases. - Shaikhani, Mohamad Abdul rahman; Mahwi, Taha Othman (Sulaimani Journal for Pure and Applied Sciences, 2001)
Background: Better selection of dyspeptic patients for UGIE to avoid the enormous costs of both overendoscopy & overtreatment is a hot topic of recent litreture ,but no fixed guidelines have been agreed upon yet. Methods: A prospective study of 1700 dyspeptic patients who had undergon UGIE in the UGIE clinic of the authors were examined & asked about common dyspeptic symptoms prior to UGIE then the statistical significance of these symptoms were measured in relation to the UGIEic results by using the qui square analysis regarding P value of < o. o5 as statistically significant Also other features of our UGIE practice were studied as shown in the text. Results:Dyspeptic symptoms can be used for better selection of patients for UGIE ,although UGIE can have reassuring effect on those with functional dyspepsia. The time needed to complete an UGIE & that needed to intubate its different levels was recorded.Dudenal ulceration was the commonest UGIE is finding ,followed by reflux oesophagitis,antral gastritis & carcinoma stomach Aoesophagus .Pyloric ring appearance had a positive predictive value offending a duodenal pathology.
Keywords: Upper GI endoscopy; Dyspeptic symptoms nonulcer Dyspepsia H Pylor